2005
DOI: 10.1111/j.1399-0004.2005.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous identification of chromosomes 18, X and Y in uncultured amniocytes by using multi-primed in situ labelling technique

Abstract: The aim of this study is to validate the multi-PRINS (primed in situ labelling) technique for simultaneous detection of chromosomes 18, X and Y in uncultured amniocytes for prenatal diagnosis of aneuploidy. The sites of the newly synthesized DNA sequences were showed as fluorescent signals by using immunochemistry. A multi-PRINS technique was specifically performed for simultaneous detection in the same cells of three chromosome targets, e.g. chromosomes 18, X and Y. Fluorescent signals corresponding to chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These modern techniques include the aforementioned FISH method, multi-primed in situ labeling (multi-PRINS), quantitative fluorescence polymerase chain reaction (QF-PCR) and multiplex ligation-dependent probe amplification (MLPA). [1119202122] There have been few studies on the applications of molecular cytogenetics for prenatal diagnostics in India. [1223] Moreover, there have been no publications in this area following the printing of the aforementioned articles, as per the MEDLINE search till December, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…These modern techniques include the aforementioned FISH method, multi-primed in situ labeling (multi-PRINS), quantitative fluorescence polymerase chain reaction (QF-PCR) and multiplex ligation-dependent probe amplification (MLPA). [1119202122] There have been few studies on the applications of molecular cytogenetics for prenatal diagnostics in India. [1223] Moreover, there have been no publications in this area following the printing of the aforementioned articles, as per the MEDLINE search till December, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype-phenotype studies have shown that, only one phenotype, sex, has perfection and binary correlation with genotype [28]. Techniques such as multiple-color primed in situ labelling (multi-PRINS), multiple-fluorescence in situ hybridization (multi-FISH) and comparative genomic hybridization (CGH) provide identification of molecularly differentiated sex chromosomes and DNA composition of sex chromosomes [33,34]. It possible to create new combinations defining chromosomal details of meiotic division and utilising separation of chromosomes and their transcription.…”
mentioning
confidence: 99%